Institutional Interventions for Enhancing Innovation Amongst Students : The Experiential Moderator - Kaur, Navjeet; Arora, Pallvi (Prabandhan: Indian Journal of Management, 2020)
The twenty-first century is a century of cut throat competition, globalization, cutting-edge technology, and advancement adopted for continuous betterment and improvement. Such environments of uncertainty and fluctuations ignite a need for continuous innovation across nations to achieve success in every sphere. Universities as well as higher education institutions (HEIs) of a nation are the major agents that facilitate in inculcating innovation as a habit among youth as their several initiatives play a key role for strengthening the ecosystem of innovation in the campuses that further substantiates the culture of innovation nation-wide. Considering the same, the objective of this research paper was to determine the role of HEIs to stimulate innovation amongst students and determine the world - class practices adopted by global HEIs. The study also incorporated the adoption of Kolb’s Experiential Learning approach to ignite innovation amongst students at the grass root level in a supportive innovative ecosystem.